1989
DOI: 10.1002/ddr.430160206
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in cocaine discrimination

Abstract: Goudie, A.J., M. Leathley, J. McNally, and C.R. West: Individual differences in cocaine discrimination. Drug Dev. Res. 16:123-131, 1989. This study involved an attempt to develop a screening test to select animals that would learn a cocaine drug discrimination (DD) rapidly and an analysis of factors affecting rates of acquisition of cocaine DD. Rats (n = 18) were trained initially in a conditioned taste aversion (C.T.A.) procedure with cocaine (36 mgikg). Subjects were then trained to discriminate cocaine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Interestingly, MK 212 only partially attenuated the aversive effects of the 5-HT 7 /5-HT 1A receptor agonist 8-OH-DPAT (and no attenuation on the moderately selective 5-HT 2A agonist DOI), suggesting that fluoxetine’s stimulus effects may be mediated primarily by 5-HT activity at the 5-HT 2C receptor. Similar work assessing the effects of pre-exposure to other drugs on fluoxetine-induced avoidance is limited (see [ 20 ]; for a review, see [ 53 ]); however, drug discrimination learning (DDL) procedures that are also used to determine shared stimulus properties (albeit not necessarily those associated with the drugs’ aversive effects; see [ 54 ]) support the fact that fluoxetine’s stimulus effects are primarily mediated by its actions on 5-HT. Establishing discriminative control when fluoxetine is used as a training drug in the DDL procedure has proven difficult, likely due to its long half-life (see [ 55 ]; though see [ 56 ] for a discussion of other SSRIs that have been successfully demonstrated in this design); however, several studies have demonstrated that fluoxetine generalizes to serotonergic compounds ([ 57 , 58 ]; though see [ 59 ]) and potentiates the discriminability of several compounds with serotonergic activity [ 58 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MK 212 only partially attenuated the aversive effects of the 5-HT 7 /5-HT 1A receptor agonist 8-OH-DPAT (and no attenuation on the moderately selective 5-HT 2A agonist DOI), suggesting that fluoxetine’s stimulus effects may be mediated primarily by 5-HT activity at the 5-HT 2C receptor. Similar work assessing the effects of pre-exposure to other drugs on fluoxetine-induced avoidance is limited (see [ 20 ]; for a review, see [ 53 ]); however, drug discrimination learning (DDL) procedures that are also used to determine shared stimulus properties (albeit not necessarily those associated with the drugs’ aversive effects; see [ 54 ]) support the fact that fluoxetine’s stimulus effects are primarily mediated by its actions on 5-HT. Establishing discriminative control when fluoxetine is used as a training drug in the DDL procedure has proven difficult, likely due to its long half-life (see [ 55 ]; though see [ 56 ] for a discussion of other SSRIs that have been successfully demonstrated in this design); however, several studies have demonstrated that fluoxetine generalizes to serotonergic compounds ([ 57 , 58 ]; though see [ 59 ]) and potentiates the discriminability of several compounds with serotonergic activity [ 58 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%